(untitled) (Fiep Bulletin - online, 2011)
The cuff is a part of endotracheal and tracheostomy tube that has the primary seal the trachea to facilitate ventilation and prevent aspiration of gastric contents into the lungs. There is no pre-established routine for controlling the cuff pressure in ventilated patients hospitalized in the intensive care unit. This pressure transmitted directly to the tracheal wall should allow a capillary blood flow adequate and preventing air leaks or aspiration, and injuries related. The objective of this study was to analyze the pressure cuff in patients hospitalized in the Intensive Care Unit (ICU) of the Hospital in the Alto Sertão of Paraiba and adjust them to acceptable limits in accordance with the literature. The purpose is implementing a proposed protocol to nursing monitor these pressures. This is a field exploratory study, with quantitative-qualitative approach, developed with patients in the ICU of the Regional Hospital in the period from April to May 2008. We evaluated 32 measures pressure cuff in eight (8) patients of male and female, through a gauge adapted to the end of an infusion set in the morning, afternoon and night. Measurements analyzed pressure cuffs (cuffs) of patients intubated and observed that the measures were variable and irregular on average 56.25% of the cases, showing the importance of redoubling the care of these patients. In this light we suggest the implementation of a nursing protocol for monitoring these pressures, in the morning, afternoon and evening, to establish a routine monitoring and measurement accurate to better quality of care, preventing complications.